Citizen science in ecology: a place for humans in nature. Issue 1 (26th March 2020) - Adler, Frederick R.; Green, Austin M.; Şekercioğlu, Çağan H.
Abstract: By involving the public, citizen science runs against the grain of an idealized science that leaves out the human element, and thus provides new opportunities for ecological research and society. We classify the goals of citizen science in ecology and environment into four broad categories: (1) scientific, (2) participant benefits, (3) community, and (4) policy. Although none of these goals have been well studied, we review the literature showing that these projects are most effective in tracking ecological trends over large swaths of space and time, and discuss the challenges of recruiting, training, retaining, and educating participants, maintaining and disseminating high‐quality data, and connecting with the larger community and policy. Biomedical studies, where patients participate in their own treatment in randomized trials, provide an interesting comparison with citizen science in ecology, sharing challenges in recruitment and involvement of nonscientists and ethical conduct of research. Future study will help address the ethical difficulties and enhance ways for citizen science in ecology and the environment to complement scientific discovery, involve and educate the public, and guide policy founded in science and the local community.